Конфліктна взаємодія повітряних суден при запобіганні загроз зіткнення - Павлова, С.В.; Волков, О.Є. (Управляющие системы и машины, 2017)
Запропоновано новий метод вирішення конфліктних ситуацій повітряних суден з визначенням пріоритетності кожного з них на основі побудови областей керованості та діаграм Венна. Метод спрямований на гарантований рівень безпеки при вирішенні розряджених конфліктних ситуацій повітряних суден в масштабі реального часу. Предложен новый метод разрешения конфликтных ситуаций воздушных судов с определением приоритетности каждого судна на основе построения областей управляемости и диаграмм Венна. Метод направлен на обеспечение уровня безопасности при разрешении разряженных конфликтных ситуаций воздушных судов в масштабе реального времени. Purpose: The proposed work is devoted to a new method for resolving conflict situations of aircraft with the prioritization of each aircraft based on the construction of control areas and Venn diagrams. This method is aimed at providing a guaranteed level of security in the resolution of depleted conflict situations of aircraft in real time. Methods: The proposed technology is based on a new method for resolving aircraft conflicts using Venn diagrams and determining the areas of control of each aircraft. Results: The introduction of a new technology to resolve aircraft conflicts in real time and the implementation of appropriate algorithms of such technology will ensure an effective increase in the level of safety of flights. Discussion: The new technology proposes a method for determining the areas of controllability of aircraft, which characterize the capabilities of the aircraft to change the parameters of motion at a single time and allow us to characterize the nonlinearity of the behavior of the aircraft. For the universality of the proposed method, the developed rules for the divergence of the aircraft in a dynamic conflict situation are proposed. The rules for clarity are constructed according to the pattern of Venn diagrams.